Effects of training in the cold on oxygen uptake kinetics - Säynäjäkangas, Pihla (2021)
The kinetics of oxygen uptake (VO2) describe how fast VO2 reaches steady state during transition to exercise. VO2 kinetics is an important determinant of aerobic performance because fast VO2 kinetics will lead to less O2 deficit at the onset of exercise. Pre-cooling of working muscles prior to exercise has been shown to slow the VO2 kinetic response to exercise but is not clear if cold environment without muscle pre-cooling has an effect on VO2 kinetics. There is currently only one study examining the effects of training in the cold on aerobic performance and mitochondrial biogenesis. Therefore, the aim of this study was to examine the effects of training in the cold on oxygen uptake and cardiovascular hemodynamics kinetics as well as aerobic performance. 37 untrained individuals aged 20-35 (51 % female) took part in a training intervention. 18 participants were randomly assigned to train in a climatic chamber set at 0 °C and 19 participants were randomly assigned to train in room temperature (~ 22°C). 15 participants form cold group and 19 participants from thermoneutral completed the 7-week high-intensity interval training intervention (3 training sessions/week). Before and after the training intervention, kinetics of VO2, heart rate (HR), stroke volume (SV), and cardiac output (CO) during moderate exercise as well as muscle blood flow and peak oxygen consumption (VO2peak) were assessed. The effects of training temperature on training adaptations were assessed comparing differences between the groups after training. The effects of the training intervention were studied comparing pre and post measurements and correlations between kinetic variables and changes in these variables were assessed to see what factors affected aerobic performance and adaptations to training. The results of this study showed that training in the cold did not affect training-induced adaptations of maximal aerobic performance (VO2peak and maximal cycling power), muscle blood flow or kinetics of VO2, HR, SV, and CO. However, the training intervention improved maximal aerobic performance and the rate of VO2 and HR kinetics. HR and CO kinetics correlated with maximal aerobic performance before and after training but VO2 kinetics did not. Also, the change in VO2 kinetics did not correlate with the change in maximal aerobic performance. The lack of difference between the groups indicates that training in the cold does not deteriorate training adaptations and there likely were no differences in muscle temperature between the groups during training. VO2 kinetics were faster after training and the improvement in the rate of VO2 kinetics is likely attributable to changes in activation of oxidative metabolism.